ANALISIS PENGEMBANGAN KURIKULUM DAN PENILAIAN PENDIDIKAN TINGGI VOKASI DIPLOMA/ AKADEMI PADA PENDIDIKAN ISLAM DALAM PEMBANGUNAN SDM 4.0 - Iwan Satriyo Nugroho, Iwan Satriyo Nugroho; Abdussalam, Abdussalam; Jiehad Akbar Pria Utama, Jiehad Akbar Pria Utama; Moch Irwan Hermanto, Moch Irwan Hermanto; Budiman, Budiman; Dila Sekar Arum Sari, Dila Sekar Arum Sari (Media Nusantara, 2024)
This paper is very important to describe the educational attainment of vocational higher education graduates in achieving national development in the field of human resources. The purpose of the research is to provide a complete explanation of the curriculum and assessment of higher education, vocational diploma/academics and their implementation in developing the professionalism of human resources. Vocational Education according to the Higher Education Law number 12 of 2012 explanation of article 16 paragraph 1 is education that prepares students to become professionals with high work skills/ability. The vocational higher education curriculum is prepared together with the professional community and professional organizations that are responsible for the quality of their professional services in order to meet the requirements of their professional competence. This paper intends to carry out an analysis of curriculum development and assessment of vocational higher education in accordance with the achievement of human resource development in the era of the Industrial Revolution 4.0. Based on the study of various sources and literature studies, it is necessary to develop a vocational education curriculum that is in accordance with HR competencies in the era of the industrial revolution 4.0 and relevant to answer the need for new skills, such as the ability to create and manage information technology systems. The vocational curriculum needs to implement offline and online integrated learning (blended learning).